Parkinson's Disease in the Era of a Novel Respiratory Virus Pandemic - Otero-losada, Matilde Estela (2020)
Humankind has gone through major airborne virus pandemics in the modern era. Coronavirus outbreaks have been registered in 2003 [severe acute respiratory syndrome (SARS)], 2009 [Middle East respiratory syndrome (MERS)], and 2019/2020 ongoing [CoV disease (COVID-19)]. Influenza outbreaks were documented in 1918 (post-World War I Spanish flu, H1N1 virus), 1957–1958 (Asian flu, H2N2 virus), 1968 (the Hong Kong flu, H3N2 virus), and 2009 (the swine flu, H1N1 virus). These viruses can only affect humans after mutating in their usual animal hosts, presenting as a zoonotic disease in the beginning. Unknown to the human immune system, they spread swiftly, resulting in outbreaks. Fatality rates vary from >30% for MERS, ~10% for the 1918 Spanish flu, 10% for SARS to <1% for the 2009 MERS. The number of infected people was 700 or 500 million with 2009's or 1918's H1N1 virus, respectively, 8,000 with SARS-CoV-1, and 2,500 with MERS-CoV. As of June 29th, according to the World Health Organization's daily situation report no. 161, SARS-CoV-2 has infected 10 million people, with a 4.98% case fatality rate.